Digitalisasi Layanan Pemesanan Katering UMKM Menggunakan Metode Rapid Application Development - Jeremy Johnatan; Haris Satriyawan (Pusat Riset dan Inovasi Nasional, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in the economy but often face challenges regarding operational efficiency. This study utilizes a case study of Dapur Adida, an MSME in Malang City, where order management is still conducted manually using physical logbooks and instant messaging (WhatsApp). This conventional method leads to a high risk of human error, overlapping production schedules, and inaccurate delivery addresses. This study aims to design and develop a web-based catering management information system to digitize business processes and minimize operational errors. The approach employed is Rapid Application Development (RAD), encompassing the stages of requirements planning, user design, construction, and cutover. The result of this research is a web application featuring catalog management, role-based access control (admin and customer), payment gateway integration, and real-time order status tracking. System testing using Black Box Testing demonstrated a functional validity of 100%, while Task-Based Usability Testing yielded a Success Rate of 100% with an average time efficiency of 0.92 tasks per minute. In conclusion, the system has proven effective in resolving manual recording inefficiencies and is feasible for implementation to support business scalability.